ANALISIS PENGARUH FAKTOR-FAKTOR DOMINAN TERHADAP PROBABILITAS KEPEMILIKAN RUMAH (Studi Kasus Perumahan Nuansa Hijau, Kecamatan Denpasar Utara) - Purbawijaya, I.B.N.; Suputra, I Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009)
It is known that the development of physical medium especially housing problem is needed by everybody and has already developed by the developers either in town or outside town. The houses vary started from their types, technical specification designs which are intended to be reachable by the customer. Eventhough the amenities offered by the developer such as paying installments, in reality there are still public civil servants (PNS) and private sector officers are not yet able to buy / to own a house by themselves caused by many reasons. In this research the selection of respondent was conducted using purposive sampling method. It is a research that base on the ability, knowledge and also certain consideration in selecting the respondents who are believed can make their choices and are able to answer the questioner promptly according to the related topic. The analyses were carried out using the theory of linear probability model method (LPM) and if the probable value is outside the definition (0 and 1) hence it will be overcame by using a logistic regression model. The analysis results showed that the sum of the family members have a signifant effect to the ownership of the house with a significant level of 5%. The coefficient of logistic regression was equal to 1.2142105 meaning that if family members increase one more hence the probability of the ownership of the house will increase by 0.771043 (77.10 %). The value -2log likelihood equal to 27.953 was bigger than that of X2 table (7.815). This means that simultaneously the three independent variables (earnings, work, and total of family member) have an effect toward dependent variable (ownership of house).
Keywords: housing, public civil servant, private sector officer, linear of probability model, model of logistic regression.